First metatarsal bone reconstruction using Masquelet’s technique after bone loss in open III B injury - Tanveer Ahmed Bhat; Pallav Gupta; Lone, Zubair Ahmad Lone; Mohammed Farooq Butt; Abdul Ghani; Sanjeev Gupta (International journal of research in medical sciences, 2023)
Background: Masquelet technique involves two stages for reconstruction of bony defects. During stage one decontamination and debridement is performed. The bone defect is filled by a spacer made of bone cement. After a gap of around 6 weeks, a bio-membrane is established around the cement spacer. During stage two, the cement spacer is removed and cancellous autologous bone graft is used to fill the space that was previously occupied by the cement spacer. However, there is a huge scarcity of literature on reconstruction of bone defects in foot metatarsals, especially open injuries that require soft tissue coverage also. Methods: This prospective study involved 25 patients with a minimum follow-up of 12 months. Masquelet’s technique was used to reconstruct large bony defects in metatarsals of foot in a staged manner. The primary outcome variable was union and consolidation of the bone. The secondary outcome variables included complications and functional outcome using Maryland foot score. Results: One of the patients needed a below knee amputation for extensive bone and soft tissue infection. Pin site infection was the commonest indication observed and deep infection was observed on table at the time of second stage in two patients. Both the patients needed a re-do of stage one and a new cement spacer was placed which was removed at six weeks. Hallux varus deformity was observed in two patients at the final follow-up. Excluding the patient that needed amputation, all the patients had consolidation and union at the final follow-up and the mean Maryland foot score was 79.45±8.8. Good to excellent functional outcome was observed among 91.66% patients. Conclusions: Masquelet’s induced membrane technique is a potentially fruitful method to deal with bone defects created by open fractures of metatarsals of feet. However, due to limited sample size and lack of control group, we recommend large scale randomized control trials be conducted on the subject.